1993
DOI: 10.1111/j.1365-3040.1993.tb00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of abscisic acid in chilling tolerance of rice (Oryza sativa L.) seedlings. I. Endogenous abscisic acid levels

Abstract: Changes of ABA levels in chilled rice {Oryza sativa L.) seedlings of two varieties were determined. On exposure to chilling, ABA concentration rapidly increased in the chilling-tolerant cultivar (cv. Tainung 67, TNG.67) but not in the chilling-sensitive cultivar (cv. Taichung Native 1, TN.l). Both detached shoots and roots of TNG.67 seedlings showed a significant ABA increase after exposure to chilling. TN.l seedlings could not accumulate ABA under low temperature but well-watered status. Exogenous application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 44 publications
5
57
0
1
Order By: Relevance
“…16,17) There was also a reported attempt to protect rice plants against the cold stress using an ABA analogue.18) In addition, it was shown that endogenous ABA levels were higher in cold-tolerant rice seedlings than in cold-sensitive rice seedlings after exposure to low temperatures. 19,20) Our results also demonstrated that ABA reduced the ratio of leaf rolling (Tables 1 and 2) and the electrolyte leakage (Fig. 2).…”
Section: Discussionsupporting
confidence: 64%
“…16,17) There was also a reported attempt to protect rice plants against the cold stress using an ABA analogue.18) In addition, it was shown that endogenous ABA levels were higher in cold-tolerant rice seedlings than in cold-sensitive rice seedlings after exposure to low temperatures. 19,20) Our results also demonstrated that ABA reduced the ratio of leaf rolling (Tables 1 and 2) and the electrolyte leakage (Fig. 2).…”
Section: Discussionsupporting
confidence: 64%
“…If root and shoot are exposed to low temperature, stomata cannot be closed in spite of root leaf water status. This failure of stomatal control in addition to decreased root hydraulic conductance can further aggravate chilling induced water stress (Lee et al 1993). All EBR treatments decreased the membrane injury index in maize leaves at both control and stress condition except at 7DAT in stress condition.…”
Section: Resultsmentioning
confidence: 99%
“…Low soil temperatures are known to inhibit L p and induce stomatal closure in aspen (Wan et al, 1999). It is possible that, like low root temperature (Chen et al, 1983;Lee et al, 1993) and drought (Zhang et al, 1987;Lång et al, 1994), HgCl 2 treatment triggered ABA synthesis, which directly caused stomatal closure. This could explain the slow recovery of stomatal opening following ME treatment.…”
Section: Discussionmentioning
confidence: 99%